Efficacy of sevoflurane flush out and activated charcoal filtration—a bench study - Mörtl, Maximilian; Schwaiger, Daniel; Lederer, Wolfgang; Weiss, Florentin; Chawaguta, Anesu; Wiesenhofer, Helmut; Mayhew, Chris A.; Ruzsanyi, Veronika (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2024)
Purpose A bench study to assess the elimination of sevoflurane from an anesthetic workstation using three different processing methods. Methods Sevoflurane concentrations from samples of the inspiratory breathing hose and air samples from within the investigation room were assessed during predetermined flush out intervals using Gas Chromatography-Ion Mobility Spectrometry. The primary objective was to determine the time to reach concentrations below 5 ppm v . Results Reduction of sevoflurane volume concentrations below a threshold of 5 ppm v was achieved within the first minute after removal of the vaporizer and the complete exchange of the soda and the breathing system and within the 15 min measurement interval after inclusion of two activated charcoal filters without a 90 s of flushing and without changing of the breathing hoses as required by the manufacturer. Conclusions Complete removal of the vaporizer and an exchange of the soda and the ventilation unit most quickly reduced sevoflurane concentrations, but the total processing interval may exceed 30 min. Inserted activated charcoal filters without a previous 90 s of flushing and without changing the breathing hoses followed by flushing only with raised fresh gas flow allow ventilation below trigger threshold to be reached within due time.